LB0001 Efficacy and Safety of Subcutaneous Belimumab plus Standard Care in Patients with Systemic Lupus Erythematosus (SLE) with Low Complement and Positive Anti-DSDNA. (15th July 2016) - Doria, A.; Stohl, W.; Schwarting, A.; Okada, M.; Scheinberg, M.; van Vollenhoven, R.; Hammer, A.E.; Groark, J.; Bass, D.; Fox, N.L.; Roth, D.; Gordon, D.
Abstract : Background: In post hoc analyses of the BLISS trials, patients with SLE with positive anti-dsDNA and low complement (C3/C4) had a greater response to intravenous belimumab (BEL) compared with patients without these characteristics. 1 Objectives: To assess the efficacy and safety of subcutaneous (SC) BEL plus standard SLE care (SoC) in patients with SLE with low C3/C4 and positive anti-dsDNA. Methods: BLISS-SC (BEL112341; NCT01484496 ) was a randomised, double-blind, multicentre, placebo-controlled trial. Patients with SELENA-SLEDAI (SS) ≥8 were randomised (2:1) to weekly BEL 200 mg SC or placebo (PBO), plus SoC. The primary endpoint was the SLE Responder Index 4 (SRI4; ≥4-point decrease in SS, <0.3 increase in Physician's Global Assessment, and no new BILAG A or ≤1 BILAG B organ domain scores, from baseline) at Week 52. Secondary endpoints included time to severe flare and reduction in steroid dose. Adverse events (AEs) were used to assess safety. Efficacy and safety data have been presented 2 ; here, data are reported for a subset of patients who were anti-dsDNA positive and hypocomplementemic at baseline. Results: Of 839 patients randomised, 356 had low C3/C4 and positive anti-dsDNA; baseline characteristics were similar between groups. At Week 52, SRI4 response was PBO 47.2% vs BEL 64.6% (odds ratio: 2.23 [95% CI 1.36, 3.64]; p=0.0014); SRI components were statistically significant. The BEL group was 62% less likely to experience a severe flare vs PBO (hazard ratio: 0.38 [95% CI 0.24, 0.61]; p<0.0001); median time to first severe flare among those having a severe flare was PBO 126.5 vs BEL 90.0 days. Numerically but not statistically (p=0.0844) more patients reduced steroid dose by ≥25% to ≤7.5 mg/day during Weeks 40–52 in the BEL group (20.7%) vs PBO (11.4%). AE incidence was PBO 81.5%, BEL 78.2%; the most common (≥10% in either group) were headache (PBO 9.3%, BEL 10.5%) and nasopharyngitis (PBO 4.6%, BEL 10.1%). Serious AE incidence was PBO 23.1%, BEL 13.3%; none occurred in ≥2.0% of patients. There were 5 deaths (PBO 1.9%, BEL 1.2%). The incidence of depression was PBO 2.8%, BEL 4.4%, with 1 case of suicide ideation (BEL 0.4%). Conclusions: Patients with SLE with low C3/C4 and positive anti-dsDNA had significantly greater SRI4 responses and fewer severe flares with BEL 200 mg SC vs PBO (plus SoC). The treatment effect for SRI4 response was numerically larger compared with the overall population. 2 Safety in both groups was similar. References: Van Vollenhoven RF et al. Ann Rheum Dis 2012;71(8):1343–9 Stohl W et al. Arthritis Rheumatol 2015;67(S10) Acknowledgement: Study funded/conducted by GSK and HGS. Louisa Pettinger, PhD, Fishawack Indicia Ltd, UK, provided editorial support, funded by GSK. Disclosure of Interest: A. Doria Grant/research support: Italian Association of Lupus patients, Consultant for: Pfizer; GSK, Speakers bureau: GSK; Eli Lilly, W. Stohl Consultant for: Eli Lilly; Jansen; Akros Pharma; Sanofi, A. Schwarting Consultant for: GSK; Actelion, M. Okada Speakers bureau: Santen Pharmaceutical; Mitsubishi Tanabe Pharma; Pfizer; Abbott Japan, M. Scheinberg Consultant for: Pfizer; GSK; Epirus; Samsung Bioepis; Janssen, R. van Vollenhoven Grant/research support: AbbVie; BMS; GSK; Pfizer; Roche; UCB, Consultant for: AbbVie; Biotest; BMS; Crescendo; GSK; Janssen; Lilly; Merck; Pfizer; Roche; UCB; Vertex, A. Hammer Shareholder of: GSK, Employee of: GSK, J. Groark Shareholder of: GSK, Employee of: GSK, D. Bass Shareholder of: GSK, Employee of: GSK, N. Fox Shareholder of: GSK, Employee of: GSK, D. Roth Shareholder of: GSK, Employee of: GSK, D. Gordon Shareholder of: GSK, Employee of: GSK